IMPLIKASI POLA ASUH ORANG TUA TERHADAP PEMAHAMAN DAN PELAFALAN ANAK - Shadrina, Zhafirah Najwa Nur; Dzaki, Muhammad Wildan; Putra, Dona Aji Karunia (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the relationship between family parenting patterns, verbal stimulation, and phonological development in three-year-old children. A qualitative descriptive method was employed, combining direct observation and audio recordings of the child’s verbal responses. The results indicate that the child’s receptive language is fairly well developed, able to understand instructions and provide meaningful responses. However, expressive language shows difficulties, with frequent mispronunciations, consonant cluster reductions, sound substitutions, and syllable shortening, related to immature speech organs and limited verbal stimulation from the family. Permissive parenting, including the use of gadgets as distractions and limited verbal guidance, reduces opportunities for consistent pronunciation modeling. Although informal family interactions occasionally provide positive reinforcement, their irregularity is insufficient to correct persistent phonological errors. Overall, this study highlights that consistent verbal stimulation and responsive parenting are crucial for phonological development at age three, a period of rapid language growth that still requires continuous guidance.